Upgraded Junker Medium Frequency Melting Furnaces - D. Trauzeddel; D. Schluckebier; F. Donsbash (Литьë и металлургия)
Is given а brief survey of the existing induction furnaces as well as the main merits of melting technologies in Junker medium frequency furnaces are advanced